Evaluación de la eficiencia del consumo de gas para generación de energía eléctrica en Colombia con base a la norma ISO 50000 (2021)
In this monographic study, gas consumption for power generation in thermoelectric plants in Colombia was evaluated. First, a bibliographic review was carried out to have context of how the studies on efficiency in thermoelectric plants, hotels and industries are progressing following the ISO 50000 methodology. For the evaluation, gas consumption and power generation data offered by the XM page were taken, with these data a Pareto diagram was built in order to focus on the thermoelectric plants with the highest gas consumption, the data of each chosen central was Filtered using the Absolute Median Deviation method, these already filtered were used to elaborate an energy baseline and obtain a normalized equation, with the help of this equation, savings percentages, critical energy generation and some established energy performance indicators were estimated. in ISO 50001 and 50006. The results of the study showed that the TEBSAB plant has consumed 51.50% of the fuel in the last three years and this presents a potential saving of 5.9%, the FLORES IV, FLORES 1 and PROELECTRICA plants have a higher percentage of savings 15, 95 %, 18.06% and 15.34% respectively, which can be explained by means of the one hundred base indicator, where it is shown that these plants have a continuous variation between compliant and non-compliant performance values.